Pengaruh Lingkungan Organisasi, Motivasi Kerja dan Disiplin Kerja terhadap Komitmen Karyawan (Studi pada Kantor BPBD Daerah Istimewa Yogyakarta) - Garut, Aloisius Agal; Prayekti, Prayekti; Chandra, Kusuma (Universitas Batanghari Jambi, 2024)
This research aims to examine the influence of the organizational environment, work motivation and work discipline on employee commitment. The research took samples at the Yogyakarta Special Region BPBD office. The sampling technique used a non-probability sampling technique using saturated sampling (census). The sample in this study consisted of 50 employees who worked at the Yogyakarta Special Region BPBD office. In this research, multiple regression analysis techniques were used. The results of the research show that simultaneously environmental factors, motivation and work discipline influence employee commitment, but partially only work environmental factors have a significant influence on employee commitment at the Yogyakarta Special Region BPBD Office